PERANCANGAN SISTEM REKOMENDASI TEMPAT PRAKTEK KERJA LAPANGAN MENGGUNAKAN FUZZY TSUKAMOTO - Akbar, Ismail; Nurdiyansyah, Firman (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2018)
In the world of work requires human resources are honest, satisfactory, clever, smart, qualifiedand competent in a controlled field. So in this case the University of Widyagama Malang requiresevery student to take the course of practical work. However, it is still not perfect in this practicalwork, because students choose the workplace practices that are not in accordance with thedominated field. In this case, the researcher applies a fuzzy tsukamoto method to recommend thepractice workplace in accordance with the student-controlled field based on some course grades.Based on the calculation using fuzzy tsukamoto method there is a workplace order or list ofagencies with the smallest value that will be the result of calculation in the workplace practicerecommendation